Figurative Language Expressions in English Language Selected Videos Posted in TikTok Application - Nabila, Succia Putri; Azwandi, Azwandi; Sujarwati, Iis (UNIB Press, 2024)
The purpose of this study is to describes the types of figurative language found in English selected videos from TikTok application. And also, tried to find out the functions of figurative language in these selected videos. A descriptive qualitative was undertaken to investigate the research question in this study. The result of the study showed that there are eleven types of figurative language found in these videos. Including simile, personification, apostrophe, synecdoche, metonymy, symbol, allegory, paradox, hyperbole, understatement and irony. Simile, synecdoche, symbol, allegory, and paradox are the dominant type found in the selected videos. Meanwhile there are five functions of figurative language discovered through the videos consist of referential function, expressive function, conative function, poetic function and phatic function. The poetic function is the most one used in the selected videos. The use of figurative language in some selected videos from TikTok application it might contains beatify meaning and also non literal meaning. Some creators of the videos used figurative language to share their opinion about love, live, daily life and also sensitive topic.